Cerebrospinal fluid untargeted metabolomic profiling of aneurysmal subarachnoid hemorrhage: an exploratory study. (2nd November 2018) - Lu, Alex Y.; Damisah, Eyiyemisi C.; Winkler, Ethan A.; Grant, Ryan A.; Eid, Tore; Bulsara, Ketan R.
Abstract: Introduction: Despite advancements in medical and surgical therapies, clinical outcomes of aneurysmal subarachnoid hemorrhage (aSAH) continue to be poor. Currently, aSAH pathophysiology remains poorly understood. No aSAH biomarkers are commonly used in the clinical setting. This exploratory study used metabolomics profiling to identify global metabolic changes and metabolite predictors of long-term outcome using cerebrospinal fluid (CSF) samples of aSAH patients. Methods and methods: Gas chromatography time-of-flight mass spectrometry was applied to CSF samples collected from 15 consecutive high-grade aSAH patients (modified Fisher grade 3 or 4). Collected CSF samples were analyzed at two time points (admission and the anticipated vasospasm timeframe). Metabolite levels at both time points were compared and correlated with vasospasm status and Glasgow Outcome Scale (GOS) of patients at 1 year post-aSAH. Significance level was defined as p  < 0.05 with false discovery rate correction for multiple comparisons. Results: Of 97 metabolites identified, 16 metabolites, primarily free amino acids, significantly changed between the two time points. These changes were magnified in modified Fisher grade 4 compared with grade 3. Six metabolites (2-hydroxyglutarate, tryptophan, glycine, proline, isoleucine, and alanine) correlated with GOS at 1 year post-aSAH independent of vasospasm status. When predicting patients who had low disability (GOS 5 vs. GOS ≤4), 2-hydroxyglutarate had a sensitivity and specificity of 0.89 and 0.83 respectively. Conclusions: Our preliminary study suggests that specific metabolite changes occur in the brain during the course of aSAH and that quantification of specific CSF metabolites may be used to predict long-term outcome in patients with aSAH. This is the first study to implicate 2-hydroxyglutarate, a known marker of tissue hypoxia, in aSAH pathogenesis.